The story of the Easter robin - Mackall, Dandi Daley (Legend series, 2010)
Tressa is worried that the robins nesting on her grandmother's window ledge will not survive a pre-Easter cold snap, but her grandmother urges her to trust that God is caring for them, as a robin once cared for His son, Jesus.